A Study of Research Trends on Education for Sustainable Development in China through Social Network Analysis - Ding, Xiu-Ying; Cho, Boo-Kyung (International Journal of Engineering and Technology, 2019)
The purpose of this research is to provide implications for researches on the education for sustainable development in China by analyzing the network between keywords in the researches on the education for sustainable development. To this end, a total of 1186 papers for academic journals and degree published over the last 10 years were collected from CNKI(China National Knowledge Infrastructure), the leading Chinese academic paper research site. After the keyword refinement process of the collected paper, the top 20 keywords were obtained, and the analysis results were expressed as a keyword network map through Net Miner 4 after conducting a centralization analysis of 20 keywords using UCINET 6. As a result, it was found that ‘vocational education’ appeared most frequently with ‘education for sustainable development’, followed by ‘environment’. As a result of the centrality analysis, it was found that ‘environment’ and 'teaching’ are hight. This shows that research on education for sustainable development in China is focused mainly on 'environment' and ‘vocational education’ and that schools are conducting education for sustainable development through various curricula. This suggests that the study of education for sustainable development should be conducted in a broader and more diverse way. Education for sustainable development is mainly conducted through classes, and research on educational goals, contents and methods are required, and measures are needed to enhance teachers' systematic understanding and awareness of sustainable development education.
Keywords: Education for Sustainable development; Social networking analysis; Environment; Vocational Education